Chapter 2.4 Steps towards decolonising contact improvisation in the university - Ashley, Tamara (Taylor & Francis, 2024)
To engage critically in a process of decolonisation is complex in a post-colonial, globalised world in which migration, knowledge exchange, hybridity and fusion are commonplace. What is it to look openly to other cultures for inspiration and guidance while also holding anti-racist decolonising attitudes? How can contact improvisation, for example, be decolonised? How are its foundations in post-modern dance, Buddhism and martial arts made sense of in current contemporary discourses of decolonisation? What is interesting about the development of contact improvisation is that despite its roots in the inclusive politics of the 1970s American counter-culture, the form is acknowledged as predominantly white and yet it draws heavily upon aikido, and in the approaches developed by Nancy Stark Smith, Tibetan Buddhism. Recent thinking and research invite deeper examination of what it might mean to decolonise contact improvisation as a practice for the 21st century curriculum. This chapter discusses the decolonisation of the teaching of contact improvisation in the university. When oppressions and obstacles are institutionally and systemically inherent, as with racism, it is not only ethically agile to develop teaching and learning dialogues that deconstruct such oppressions but ethically necessary.